2022
DOI: 10.1002/csc2.20797
|View full text |Cite
|
Sign up to set email alerts
|

Oil and seed yields affected by sowing dates and irrigation regimes applied in growth phenological stages of safflower

Abstract: Research establishing optimal sowing dates and irrigation can help to alleviate the adverse effects of drought on safflower (Carthamus tinctorius L.). The main objective of this study was to assess the effects of sowing date and irrigation quantity on safflower traits. Irrigation treatments were applied based on crop evapotranspiration (ET c ) at the vegetative, flowering, and capitulum development stages. Evapotranspiration increased as the number of irrigations increased. Morphological, yield and oil traits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…As a result, the lower carbon uptake led to a lower seed yield in oilseed rape genotypes. The results of a study on safflower under water deficit stress at different growth stages showed that water supply at the flowering and capitulum development stages improved the water use efficiency and seed yield of safflower [35]. Pradawet et al [36] studied maize crops under normal and dry stress conditions and found a significant correlation between the plant water stress index and stomatal conductance (R 2 = 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the lower carbon uptake led to a lower seed yield in oilseed rape genotypes. The results of a study on safflower under water deficit stress at different growth stages showed that water supply at the flowering and capitulum development stages improved the water use efficiency and seed yield of safflower [35]. Pradawet et al [36] studied maize crops under normal and dry stress conditions and found a significant correlation between the plant water stress index and stomatal conductance (R 2 = 0.90).…”
Section: Discussionmentioning
confidence: 99%
“…The number of capitula showed significant differences among the analyzed treatments, with the treatment that received irrigation only during its reproductive stage having the highest mean (5.00) compared to the others (Table 5). Baseri et al (2022), in their work on safflower with different sowing times and irrigation regimes applied during phenological growth stages, also demonstrated better results for the number of capitula in treatments with supplementary irrigation during the reproductive stage.…”
Section: Greenhouse Experimentsmentioning
confidence: 95%
“…Kumar Barla et al (2020) reported that there was no significant difference between combination of sowing dates and safflower cultivar for number of seeds per head. Gholami Baseri et al (2022) emphasized that late sowing can reduce the number of seeds per head in safflower.…”
Section: Number Of Seeds Per Headmentioning
confidence: 99%